Impact Of Electronic Word Of Mouth And Influencer On Buying Decisions (Survey On Skincare Somethinc Consumer Products In The University Environment Of Tasikmalaya) - Milawatul Aulia; Askolani Askolani; Ari Arisman (Penerbit Jurnal Indonesia, 2023)
This study aims to determine and analyze the influence of electronic word of mouth and influencers simultaneously and partially on consumer purchasing decisions for Somethinc products in the Universitas Perjuangan Tasikmalaya environment. The method used in this research is descriptive analysis method. The data used in this study are primary data derived from questionnaires that have been distributed to consumers using Something skincare. Data analysis in this study used multiple linear regression analysis, correlation coefficient, and determination coefficient using SPSS version 26 software. The results of this study are that Electronic Word of Mouth has a significant effect on Purchase Decisions. Influencers have a significant effect on purchasing decisions. In the simultaneous test, Electronic Word of Mouth and Influencers have a significant effect on purchasing decisions.